2021
DOI: 10.1093/aob/mcab112
|View full text |Cite
|
Sign up to set email alerts
|

Pollen limitation and xenia effects in a cultivated mass-flowering tree, Macadamia integrifolia (Proteaceae)

Abstract: Background and Aims Pollen limitation is most prevalent among bee-pollinated plants, self-incompatible plants, and tropical plants. However, we have very little understanding of the extent to which pollen limitation affects fruit set in mass-flowering trees despite tree crops accounting for at least 600 million tons of the 9,200 million tons of annual global food production. Methods We determined the extent of pollen limitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(73 citation statements)
references
References 90 publications
4
37
1
Order By: Relevance
“…Currently, orchards are established with single‐cultivar blocks (Trueman, 2013; Vithanage et al., 2002) that could be, for example five rows wide (as in the narrow‐block orchard) or 48 rows wide (as in the wide‐block orchard). However, we have shown that the number of harvested nuts of cultivar 816 was reduced by three rows into the wide block, where the distance to another cultivar, Daddow, was 24 m. A recent study found that supplementary cross‐pollination increased yields of two cultivars, 816 and Daddow, and that the yield increase was greater when the experimental trees were far from another cultivar, suggesting that the flow of cross‐pollen across the orchard was suboptimal (Trueman et al., accepted). Yields of cultivar A16 trees have also been shown to decline by 14 rows into a wide block, where the distance to another cultivar, A4, was 98 m (Vithanage et al., 2002).…”
Section: Discussionmentioning
confidence: 83%
“…Currently, orchards are established with single‐cultivar blocks (Trueman, 2013; Vithanage et al., 2002) that could be, for example five rows wide (as in the narrow‐block orchard) or 48 rows wide (as in the wide‐block orchard). However, we have shown that the number of harvested nuts of cultivar 816 was reduced by three rows into the wide block, where the distance to another cultivar, Daddow, was 24 m. A recent study found that supplementary cross‐pollination increased yields of two cultivars, 816 and Daddow, and that the yield increase was greater when the experimental trees were far from another cultivar, suggesting that the flow of cross‐pollen across the orchard was suboptimal (Trueman et al., accepted). Yields of cultivar A16 trees have also been shown to decline by 14 rows into a wide block, where the distance to another cultivar, A4, was 98 m (Vithanage et al., 2002).…”
Section: Discussionmentioning
confidence: 83%
“…This apparently anomalous phenomenon was first described by Darwin as “the direct action of the male element on the female form” and subsequently called ‘xenia’. Xenia is widespread in cultivated species, including cereals, vegetables and fruit trees (Trueman et al, 2021). To the best of our knowledge, however, no reports exist of xenia in Capsicum (Liu, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Tree yields can be constrained by the percentage of flowers that are pollinated and fertilised, the percentage of fruit that develop to maturity, and the mass of the fruit components that contribute to yield [9][10][11][12]. Mass-flowering trees, which include many of the world's tropical and subtropical tree crops, typically produce many more flowers than mature fruit [9,[13][14][15]. Many of the flowers do not set fruit and many of the fruit abscise during the early fruit development period [9,14,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Many of the flowers do not set fruit and many of the fruit abscise during the early fruit development period [9,14,[16][17][18]. The final size of the remaining fruit that reach maturity can be affected by environmental conditions [19,20], crop nutrition [21][22][23] and fruit paternity [15,[24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%